Existing Line Correction Based on Cuckoo Algorithm - Wenkun WANG (机车电传动)
Using proper line correction optimal design parameter can reduce overall adjustment quantity of line correction and maintenance. An existing line correction method based on the cuckoo search algorithm was proposed in this paper. First, equation of straight line between curves was established by least square method, and each feature points were identified and calculated. Then with the minimum sum of the absolute value of the line adjustment quantity of each measuring point as optimization goal, with intercept and slope of straight line between curves, length of transition curve and circular curve radius as independent variable, a model was established by using cuckoo search algorithm, and the optimization design parameters of line correction were obtained by solving. In order to verify the effectiveness of the algorithm, the plane measurement coordinates of a certain section of the Shanghai-Kunming line were used as the test object. Under the conditions of unconstrained, overall constraint, and single-point constraint, the overall adjustment quantity obtained by optimization was smaller than traditional method. The results showed that the optimal design parameters obtained by this method could make line adjustment quantity smaller than previous methods, and have the advantages of strong data processing applicability and more accurate calculation results.